2015
DOI: 10.15740/has/au/10.1/48-51
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the information seeking behaviour of the ber growers

Abstract: The present study was under taken in ber growing area of Rajasthan to know the information behaviour of ber growers. For the study 100 ber growers were selected by using random sampling method. Statistical analysis was done to inferences the result. it was observed that majority of ber growers were having medium level of information seeking behaviour. The association between the information seeking behaviour of ber growers and the selected independent variables viz., age, education level, social participation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
3
5
1
Order By: Relevance
“…This shows that there was no significant difference between the peripheral and distant Guava farmers in their information seeking behavior. The findings are in line with the findings obtained by Dhayal et al, (2009), Nitharwal (2011), Meena (2012) and Meena et al, (2013).…”
Section: Information Seeking Behavior Of the Guava Farmerssupporting
confidence: 92%
“…This shows that there was no significant difference between the peripheral and distant Guava farmers in their information seeking behavior. The findings are in line with the findings obtained by Dhayal et al, (2009), Nitharwal (2011), Meena (2012) and Meena et al, (2013).…”
Section: Information Seeking Behavior Of the Guava Farmerssupporting
confidence: 92%
“…Regarding demographic factors, farmers’ levels of education are significantly positively correlated with the INS, whereas age, gender, family size, and farming income have no significant relationship with the INS. Several past studies have also shown relationships between different demographic factors and farmers’ information needs (Dhayal et al , 2013; Gunawardana and Sharma, 2006). Thus, it is clear that depending on the context considered, various demographic factors influence farmers’ information needs.…”
Section: Resultsmentioning
confidence: 97%
“…Several investigations have been carried out to investigate the ISB in agriculture (e.g. Aziagba and Okede, 2011; Dhayal et al , 2013; Gunawardana and Sharma, 2006; Elly and Silayo, 2013; Kabir et al, 2014; Okwu and Daudu, 2011; Pezeshki-Rad and Zamani, 2005; Walisadeera et al , 2015). Past studies have disclosed that demographic (Dhayal et al , 2013; Gunawardana and Sharma, 2006), socio-economic, and cultural factors (Gunawardana and Sharma, 2006) are significantly related to farmers’ ISB.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations